Constructing the site: Discourse and mapping beyond the site survey - Trostek, Sanna (My University, 2024)
This thesis explores site-specificity in order to develop a deeper knowledge of the site analysis’ effect on design and its narrative. Using discourse on site-specificity and space, the aim is to understand and expand the notion of site, space, and site-specific and how this relates to urban design. To expand the notion of site and connecting the thesis to discourse, seven aspects of site were identified. The aspects are site as locale, border, context, time, narrative, construct, and imagination. To tie the aspects to spatial practices they were connected to Lefebvre’s spatial triad of conceived space, perceived space, and lived space, as well as to David Harvey’s definition of absolute, relative, and relational space. In the thesis each aspect and type of space is associated with, or captured in, a type of architectural representation. Photographs taken by the author in the neighbourhood, for example, represents the locale aspect of site with the perceived and absolute space, while data of noise pollution can be associated within the perceived and relational space with site as border. The goal of mapping the site was to create a method which could be used as a guide for site analysis, and create an artefact, an “atlas” of the site and its spaces. The atlas is an assemblage of diagrams, archive drawings, photographs, maps, and geodata, from which a site-specific design could depart. When fragments of representations are assembled into the atlas, a new complex and multi-layered understanding of the site and space emerges. This method is further contextualised by connecting theories of site specificity within art to architecture. The mapping was used for research and analysis of a site in the suburban neighbourhood unit of Norra Guldheden in Gothenburg, characterised by its greenery and Folkhem housing. The atlas is used to create site-specific design interventions, that depart from the identified space. The interventions are designed to enhance the space, and connect it to other contexts, thereby contributing to the production of space. In conclusion, the thesis uses mapping and spatial discourse to analyse and ultimately construct the site rather than take it for granted.
Keywords: site, mapping, space, site analyse, site-specific